The Significance of Cultural Objects in the Development of Tourism in Fergana Region - Kadirova Dildora Sabirdjanovna (Zien Journals, 2023)
In this article, the importance of cultural objects in the development of tourism in the regions of Fergana region and its problems are determined. Based on the 5 main tourist indicators, each group was analyzed. Also, existing but poorly developed tourism farms in the region were analyzed, problems were identified and practical suggestions were drawn up.
Keywords: Tourist area; infrastructure; index; ecotourism